2015
DOI: 10.1111/jcpt.12308
|View full text |Cite
|
Sign up to set email alerts
|

Drug-drug interaction between isavuconazole and tacrolimus: a case report indicating the need for tacrolimus drug-level monitoring

Abstract: Summary What is known and objective Despite the known significant drug-drug interaction between isavuconazole and tacrolimus there are no recommendations on dose-adjustment when these drugs are given concomitantly. We report on a patient with a mediastial Aspergillus fumigatus infection resistant to posaconazole and describe how she was successfully managed with isavuconazole therapeutic drug-level monitoring. Case description Our patient presented with a mediastial Aspergillus fumigatus infection, two year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 2 publications
1
29
0
Order By: Relevance
“…Moreover, Groll included young (mean age, 35 years), healthy volunteers who were on no other drugs, whereas our patients were older (mean age, 60 years), critically ill, and within a month of transplant. Our results, combined with the considerable interpatient variability in the magnitude of the drug interaction (11), suggest that tacrolimus should not be administered using uniform dose reductions among patients receiving isavuconazole, but rather guided by therapeutic drug monitoring. This conclusion differs from the standard dose reductions that are recommended when initiating or discontinuing voriconazole or posaconazole (4,5).…”
mentioning
confidence: 87%
“…Moreover, Groll included young (mean age, 35 years), healthy volunteers who were on no other drugs, whereas our patients were older (mean age, 60 years), critically ill, and within a month of transplant. Our results, combined with the considerable interpatient variability in the magnitude of the drug interaction (11), suggest that tacrolimus should not be administered using uniform dose reductions among patients receiving isavuconazole, but rather guided by therapeutic drug monitoring. This conclusion differs from the standard dose reductions that are recommended when initiating or discontinuing voriconazole or posaconazole (4,5).…”
mentioning
confidence: 87%
“…One study in healthy adults reported increases in tacrolimus and sirolimus exposure when combined with isavuconazole . One study and one case report in solid organ transplant patients also indicated increases in tacrolimus exposure when combined with isavuconazole . However, one case report in an alloHSCT patient indicated that no empiric dose reduction in tacrolimus was needed when combined with isavaconazole …”
Section: Introductionmentioning
confidence: 99%
“…However, we increased the interval between TAC doses. The level of interaction between isavuconazole and immunosuppressive agents did not appear to be as high as has been reported for other triazole antifungal agents . In a recent report, the interaction between isavuconazole and TAC differed by the transplanted organ, with considerable interpatient variability .…”
Section: Discussionmentioning
confidence: 61%